2020
DOI: 10.1016/j.msea.2020.140108
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of Ca segregation on thermal stability, electrical resistivity and mechanical strength of nanostructured aluminum

Abstract: Achieving a combination of high mechanical strength and high electrical conductivity in lowweight Al alloys requires a full understanding of the relationships between nanoscaled features and physical properties. Grain boundary strengthening through grain size reduction offers some interesting possibilities but is limited by thermal stability issues. Zener pinning by stable nanoscaled particles or grain boundary segregation are well-known strategies for stabilizing grain boundaries. In this study, the Al-Ca sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 61 publications
(122 reference statements)
0
14
0
Order By: Relevance
“…The absence of solubility in the Al-8% Ca binary alloy during HPT through five turns was previously shown using synchrotron radiation X-ray method. [14] At the same time, when studying the Al-12% Ca alloy, [20] it was shown that at a high number of turns (N ¼ 100), calcium are formed along the crystallite boundaries, causing additional alloy hardening. It should be noted that the Al-12% Ca alloy was obtained not by casting, [20] but by mixing Al and Ca powders, and the initial structure was not analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of solubility in the Al-8% Ca binary alloy during HPT through five turns was previously shown using synchrotron radiation X-ray method. [14] At the same time, when studying the Al-12% Ca alloy, [20] it was shown that at a high number of turns (N ¼ 100), calcium are formed along the crystallite boundaries, causing additional alloy hardening. It should be noted that the Al-12% Ca alloy was obtained not by casting, [20] but by mixing Al and Ca powders, and the initial structure was not analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…[14] At the same time, when studying the Al-12% Ca alloy, [20] it was shown that at a high number of turns (N ¼ 100), calcium are formed along the crystallite boundaries, causing additional alloy hardening. It should be noted that the Al-12% Ca alloy was obtained not by casting, [20] but by mixing Al and Ca powders, and the initial structure was not analyzed. As noted in the Introduction Section, the behavior of two-phase eutectic aluminum alloys both during casting and deformation differs significantly from the behavior of complex eutectic aluminum alloys due to the effect of chemical elements on mutual solubility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, ultra-SPD is considered an effective tool to produce a wide range of materials such as binary and ternary alloys and intermetallics [ 16 , 17 ], high-entropy alloys [ 30 ], metal hydrides [ 31 , 32 ], and high-entropy ceramics [ 33 ]. Table 1 summarizes the results of the application of ultra-SPD to different systems in the author’s group and summarizes the main achievements of each system [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. As can be seen in Table 1 , the application of ultra-SPD is not limited to the synthesis of conventional metallic alloys, and it has been recently extended to ceramic materials.…”
Section: Ultra-severe Plastic Deformationmentioning
confidence: 99%
“…The microstructure can be stabilized by second-phase particles of an immiscible element, but due to the immiscibility effect, such alloys show negligible solid solution hardening and poor age hardening [ 69 , 70 , 71 , 72 ]. Ultra-SPD provides an effective path to achieve supersaturation in various Al-based alloys such as Al-Ca [ 55 ], Al-Fe [ 49 ], Al-Zr [ 26 ], and Al-La-Ce [ 56 ]. Such a supersaturation can lead to an enhanced solution hardening effect in these alloys.…”
Section: Ultra-severe Plastic Deformationmentioning
confidence: 99%